Bank economic capital - Beverly J. Hirtle; Matthew C. Plosser (Federal Reserve Bank of New York, 2025)
Conventional measures of bank solvency fail to account for the unique liquidity risks posed by deposits. Using public regulatory data, we develop a novel measure, economic capital, that jointly quantifies the impact of credit, liquidity, and market risk on bank solvency. We validate that economic capital is a more timely and accurate indicator of bank health than standard solvency measures. Using our framework, we examine the evolution of banking sector risk exposures over several decades. Despite significant reforms in the aftermath of the Global Financial Crisis, economic capital suggests that liquidity and market risks have grown and remain elevated.
Keywords: G21; G17; G01; 330; bank capital; solvency; liquidity; financial stability